Pengaruh Pemberian Ekstrak Anggur laut (Caulerpa racemosa) Dalam Menghambat Infeksi Bakteri Aeromonas hydrophila Pada Ikan Nila (Oreochromis niloticus) - Nur Inda Sari; Patang Patang; Indrayani Indrayani (Universitas Negeri Makassar, 2022)
This study aims to determine the effect of giving sea grape extract (Caulerpa racemosa) in inhibiting Aeromonas hydrophila bacterial infection in tilapia (Oreochromis niloticus) and to determine the concentration of use of sea grape (Caulerpa racemosa) which is effective to inhibit Aeromonas hydrophila bacterial infection in tilapia (Oreochromis niloticus) and this study was an experimental study using a completely randomized design (CRD).The variables observed in this study were changes in fish behavior, fish morphology, fish anatomy, survival, water quality parameters (temperature, DO, pH). The data was processed using the SPSS Version 24 program with Analysis (ANOVA) if there were differences, then continued with Duncan.The results showed that the administration of sea grape extract (Caulerpa racemosa) could inhibit Aeromonas hydrophila bacterial infection in tilapia. The average level of inhibitory power of the extract was the best in treatment C with 25 mg/l of sea grape extract (Caulerpa racemosa) the condition of the fish improved on day 1 postoperatively. immersion and the lowest level of inhibition in the control treatment the condition of the fish was getting worse every day, having a significant effect (P<0.05), the highest survival was in treatment C where survival on day 14 was 73%. Water quality average temperature 27% C, average dissolved oxygen 5-6 ppm and average pH 7.4-7.8